(3GdGfJUGQs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3eMeO TajY Hf YHO GdhGMO ajQhRBHGOjs)
(3ChdgG (B:s
(3GdMeO ddg Ydi eG jSQ ef Mb eJHY hUQa ef HGWd eHJOY(B...(3CeG HYO aEfj eeJKd eG QSeJg GdMVQI GdSGejI (B... (3ef HjGf GdeSGFd GdabgjIs
(3BNQgG (B:s
(3dCf Pdc jOYh Edi GdMSO hGdYOGhI hdG NdGa aj LhGRg GdChd(B. (3Je GdcJGH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B2(3, U(B435s
(3GdCYdGe(B: (3L(B4(3, U(B278s
(3GdCYdGe(B: (3L(B4(3, U(B278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis